One-Step Facile Preparation and Photoluminescence Properties of Tetrakis(4-carboxyphenyl)porphyrin Functionalized Zinc Oxide Nanostructures - Liu*, Qingyun; Jia, Qingyan; Zhou, Hangyue; Gao, Chun; Shao, Qian; Li, Guijiang; Bian, Bing (Asian Journal of Chemistry, 2014)
We developed facile synthetic procedure to prepare zinc oxide nanorods functionalized with a tetrakis(4-carboxyphenyl)porphyrin molecules by a better understanding of their coordination chemistry. The obtained samples are hexagonal Wurtzite structures characterized by X-ray diffraction spectra. FTIR data verify the porphyrin functionalized zinc oxide nanorods through coordination interaction between zinc of zinc oxide nanostructures and carboxylic groups of tetrakis(4-carboxyphenyl)porphyrin molecules. TEM images reveal that optimal reaction time of the uniform nanorods with sharp tips is about 60 min. A possible formation mechanism of the zinc oxide nanorods with sharp tips has also been proposed. Photoluminescence (PL) characterization of the functionalized nanorods shows that these nanorods exhibit strong emission at 460 nm, a red-shift of about 15 nm at UV wavelength (393 nm) and special optical properties in yellow-green emission, compared with that of the corresponding nanorods and nanowires in previous reports.